Philosophy in early Safavid Iran Najm al-Dīn Mah - Pourjavady, Reza. (Islamic Philosophy, Theology and Science. Texts and Studies, 2011)
Muslim philosophical activities on the cusp of the Safavid era (i.e., late 9th/15th and early 10th/16th centuries) have so far escaped the attention of modern scholars. In Iran, the city of Shiraz was the principal center of philosophy at this time, and it was here that Najm al-Dīn Maḥmūd al-Nayrīzī (d. after 933/1526), whose life and works are the subject of this book, spent his formative years. An accomplished Shīʿī scholars, Nayrīzī engaged with Avicennan as well as Suhrawardian philosophy in his works. Beside Nayrīzī, the present study introduces his contemporaries among the philosophers of Shiraz and provides an outline of the main challenges of their thought, particularly of the two leading figures, Jalāl al-Dīn al-Dawānī (d. 908/1502) and Ṣadr al-Dīn al-Dashtakī.